1986
DOI: 10.1128/mcb.6.4.1172
|View full text |Cite
|
Sign up to set email alerts
|

The t-unique coding domain is important to the transformation maintenance function of the simian virus 40 small t antigen.

Abstract: The smail t antigen (t) of simian virus 40, a 174-amino-acid-containing protein, when present together with the other early viral protein, large T antigen (T), plays an important role in the maintenance of simian virus 40-induced neoplastic phenotype in certain cells. Indeed, each protein functions in a complementary manner in this process. The t coding unit is composed of two segments, a 5' region of 246 nucleotides which is identical to that of the corresponding 5' region of the T coding unit and a 3' segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Because others have observed that expression of small t Previous work has demonstrated that expression of SV40 large T is sufficient to transform cycling but not resting cells (5,6,8,11,14,19,36,37,41,45,46). Transformation can occur in resting cells, however, if either small t is coexpressed or the cells are treated with phorbol esters.…”
Section: Resultsmentioning
confidence: 99%
“…Because others have observed that expression of small t Previous work has demonstrated that expression of SV40 large T is sufficient to transform cycling but not resting cells (5,6,8,11,14,19,36,37,41,45,46). Transformation can occur in resting cells, however, if either small t is coexpressed or the cells are treated with phorbol esters.…”
Section: Resultsmentioning
confidence: 99%
“…ST cannot transform cells alone, although it may enhance the eciency with which transformation occurs (Bouck et al, 1978;Bikel et al, 1986;Fanning, 1992) and it can complement a LT mutant deleted for the N-terminal 82 amino acids (Montano et al, 1990). There is also evidence that 17kT can transform cells independently of LT (Zerrahn et al, 1993).…”
Section: Abstract: Sv40 T Antigens; Apoptosismentioning
confidence: 99%
“…A portion of the T155 DNA sequence also encodes SV40 small t by an alternative splicing mechanism, and the two proteins have amino acid residues 1-82 in common (Jog et al, 1990;Paucha et al, 1978). Small t is believed to be critical for the transformation of cells but is not required for immortalization (Bikel et al, 1986(Bikel et al, ,1987Bouck et al, 1978;Fanning, 1992). While the functions of small t are incompletely understood, in cells that have been subjected to SV40 infection, it is reported to enhance viral replication and polyploidy of the host cells (Whalen et al, 1999) to facilitate transformation of the infected cells by LT in limiting growth conditions (Bikel et al, 1987;Martin and Chou, 1975;Rubin et al, 1982) and to promote induction of cell cycle progression in non-dividing cells, (Porras et al, 1999).…”
Section: Discussionmentioning
confidence: 99%